1995
DOI: 10.1148/radiology.197.3.7480742
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic, endoscopic, and surgical gastrostomy: an institutional evaluation and meta-analysis of the literature.

Abstract: Radiologic gastrostomy is associated with a higher success rate than is PEG and less morbidity than either PEG or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
5
23

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(248 citation statements)
references
References 0 publications
11
205
5
23
Order By: Relevance
“…Ascites and peritoneal carcinomatosis should not be considered contraindications for radiologic gastrostomy or gastrojejunostomy. P ercutaneous radiologic gastros tomy is an alternativeto surgical or endoscopic tube placement; a metaanalysisby Wollman et al [1] and other studies have shown that the radiologic method of placement has lower rates of morbidity and mortality than either the surgical or the endo…”
Section: Materials and Methods Forty-fiveconsecutive Patientswith Asmentioning
confidence: 99%
“…Ascites and peritoneal carcinomatosis should not be considered contraindications for radiologic gastrostomy or gastrojejunostomy. P ercutaneous radiologic gastros tomy is an alternativeto surgical or endoscopic tube placement; a metaanalysisby Wollman et al [1] and other studies have shown that the radiologic method of placement has lower rates of morbidity and mortality than either the surgical or the endo…”
Section: Materials and Methods Forty-fiveconsecutive Patientswith Asmentioning
confidence: 99%
“…Percutaneous tube placement is associated with high success rate and has been suggested to be safer than other placement techniques. 9,10 Although enterostomy tube feeding has become widely accepted in children and adolescents with chronic medical illness, its use in similarly aged children and adolescents with psychiatric illness has been limited by two main concerns. First, purposeful tube manipulation in the early postinsertion period will result in serious medical complications such as peritonitis or sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of life threatening aspiration was four times lower in PRG compared with PEG, although differences possibly reflect institutional bias towards the use of a particular method in different patient categories. 20 In another recent meta-analysis of 2379 head and neck cancer patients, major complication rates following PEG and PRG were 7.4% (95% CI 5.9-9.3%) and 8.9% (95% CI 7.0-11.2%) respectively. PRG was associated with increased morbidity and mortality in those who are ineligible for PEG.…”
Section: Comparison Of Different Techniquesmentioning
confidence: 98%